An innovative solution to enhance the safety of the cactus packaging / Muhammad Shafiq Shaharuddin - Shaharuddin, Muhammad Shafiq (Universiti Teknologi MARA, Perak, 2020)
Cactus is one of the most liked plants by plant enthusiasts. Although it is a very durable plant compared to other plants, it can also be damaged if not handled with care. Conventional way of to package they plant by simply wrap the cactus using used newspaper or a magazine. Improper handling of cactus affected the cactus appearance and resulted in loss to the seller and buyer. With this in mind, the goal of this project is to produce innovative packaging which addresses this problem. Special attention was given to the print production substrate and a newly developed holder to ensure safety and ergonomics. In addition, the researchers also develop unique visuals and a cross media in the form of Augmented reality as a novelty way to engage customers to the products. Ukay Nursery was chosen for this applied research project, and has proven beneficial to this business. This project has high commercialization value since this is an applied research project and can be implemented in an actual business environment. It is hoped that this innovation will enhance the plant nursery business as a whole.